Correction: Huang et al. An Attention-Based Recommender System to Predict Contextual Intent Based on Choice Histories across and within Sessions. Appl. Sci. 2018, 8, 2426 - Ruo Huang; Shelby McIntyre; Meina Song; Haihong E; Zhonghong Ou (Applied Sciences, 2021)
We, the authors, wish to make the following corrections to our paper [1] [...]